2013
DOI: 10.1016/j.pain.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine contribution to neuropathic pain: Respective induction of CXCL1 and CXCR2 in spinal cord astrocytes and neurons

Abstract: Recent studies have indicated an important role of chemokines such as CCL2 in the development of chronic pain. However, the distinct roles of different chemokines in the development and maintenance of neuropathic pain and in their interactions with neurons have not been clearly elucidated. We found that spinal nerve ligation (SNL) not only induced persistent neuropathic pain symptoms including mechanical allodynia and heat hyperalgesia but also produced sustained CXCL1 upregulation in the spinal cord. Double s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
253
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(273 citation statements)
references
References 80 publications
16
253
1
3
Order By: Relevance
“…Role of TNF-a in Upregulation of CXCL12 in the Lumbar DRG and Spinal Cord During the Development of Neuropathic Pain Following SNI Recent studies have shown that TNF-a regulates CXCL1 release in the spinal cord following SNL at L5 [19]. Here, we found that SNI induced an increase in the expression of TNFa in the DRG and spinal cord compared to the sham group.…”
Section: Sni Increases Cxcl12 and Cxcr4 Expression In The Spinal Dorssupporting
confidence: 49%
See 2 more Smart Citations
“…Role of TNF-a in Upregulation of CXCL12 in the Lumbar DRG and Spinal Cord During the Development of Neuropathic Pain Following SNI Recent studies have shown that TNF-a regulates CXCL1 release in the spinal cord following SNL at L5 [19]. Here, we found that SNI induced an increase in the expression of TNFa in the DRG and spinal cord compared to the sham group.…”
Section: Sni Increases Cxcl12 and Cxcr4 Expression In The Spinal Dorssupporting
confidence: 49%
“…The prevailing evidence shows that TNF-a stimulates IL-1b and IL-6 release from DRGs and the spinal cord following nerve injury [38,39]. Further, the spinal nerve ligation-induced increase in the expression of CXCL1 in the L5 spinal cord is regulated by TNF-a [19] and i.t. administration of TNF-a induces the expression of monocyte chemoattractant protein-1 by spinal astrocytes [39].…”
Section: Tnf-a Might Mediate the Increased Cxcl12 Expression In The Dmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that IL-1␤ induces CXCL1 and neutrophil infiltration and TNF-␣ induces CCL2 and monocyte infiltration (Campbell et al, 2005) and that these pathways do not significantly cross over (Schnell et al, 1999;Blond et al, 2002) cord CXCL1 (Zhang et al, 2013) but demonstrations of this in the brain are lacking. Here both IL-1␤ and TNF-␣ robustly induced both CXCL1 and CCL2 in astrocytes of the degenerating brain.…”
Section: Primed Microgliamentioning
confidence: 99%
“…По данным экспериментальных иссле-дований, наряду с индукцией остеокластогенеза АЦБ об-ладают способностью вызывать болевые ощущения (меха-ническая и термальная гиперчувствительность) в отсутст-вие признаков воспаления [78]. Развитие боли также опо-средуется ИЛ8-зависимым механизмом, а именно -свя-зыванием ИЛ8 (или CXCL1) с CXC хемокиновыми рецеп-торами 1-го и 2-го типа, что приводит к сенситизации и активации сенсорных нейронов [88]. Блокада хемокинов с использованием рецепторных антагонистов отменяет как АЦБ-индуцированную потерю костной ткани, так и болевые ощущения [78].…”
Section: таблицаunclassified